Fast Correlation Attacks on Grain-like Small State Stream Ciphers - Bin Zhang; Xinxin Gong; Willi Meier (IACR Transactions on Symmetric Cryptology, 2017)
In this paper, we study the security of Grain-like small state stream ciphers by fast correlation attacks, which are commonly regarded as classical cryptanalytic methods against LFSR-based stream ciphers. We extend the cascaded structure adopted in such primitives in general and show how to restore the full internal state part-by-part if the non-linear combining function meets some characteristic. As a case study, we present a key recovery attack against Fruit, a tweaked version of Sprout that employs key-dependent state updating in the keystream generation phase. Our attack requires 262.8 Fruit encryptions and 222.3 keystream bits to determine the 80-bit secret key. Practical simulations on a small-scale version confirmed our results.